2021
DOI: 10.3389/fchem.2021.732935
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Colorimetric Fluoride Anion Sensor Based on π-Conjugated Carbazole Small Molecule

Abstract: The ability to detect fluoride anions with high selectivity and sensitivity by using the naked eye is crucial yet challenging. In this study, a novel, simple conjugated organic dye, N-tert-butyldimethylsilyl-3,6-diiodocarbazole (CA-TBMDS) was developed and used for the first time as a colorimetric sensor for fluoride. CA-TBMDS was found to be a highly sensitive fluoride chemosensor, with a detection limit as low as 3 × 10−5 M. The reaction of CA-TBMDS with fluoride anions in a tetrahydrofuran solution resulted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…2b ). The combination of conformations of the two Hdpa ligands in 1 2+ has also been observed in [Ru(bpy)(Hdpa) 2 ](ClO 4 ) 2 , 18 but not in the starting complex cis -[RuCl(dmso- S )(Hdpa) 2 ] + (P1 + ). 29 Each Hdpa ligand in P1 + captured a monodentate ligand, Cl, or a methyl group of the dmso- S ligands using two pyridyl groups, resulting in both NH groups being close to each other ( syn -NH conformation, Fig.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…2b ). The combination of conformations of the two Hdpa ligands in 1 2+ has also been observed in [Ru(bpy)(Hdpa) 2 ](ClO 4 ) 2 , 18 but not in the starting complex cis -[RuCl(dmso- S )(Hdpa) 2 ] + (P1 + ). 29 Each Hdpa ligand in P1 + captured a monodentate ligand, Cl, or a methyl group of the dmso- S ligands using two pyridyl groups, resulting in both NH groups being close to each other ( syn -NH conformation, Fig.…”
Section: Resultsmentioning
confidence: 85%
“…Both angles were consistent with those of the Hdpa ligand in previously reported Ru( ii )–Hdpa complexes (25.9–48.2°). 18,29,39,40 The difference between the two dihedral angles is likely caused by steric interactions between H 2 pia and the two Hdpa ligands. The N2 atom of the NH group in Hdpa( N 1, N 3) established contact with the O1 atom of H 2 pia (N2⋯O1 = 3.036 Å; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 48 Quite recently, a small molecule, N -tertbutyldimethylsilyl-3,6-diiodocarbazoles a conjugated organic dye, was design, constructed and employed as a selective fluoride colorimetric sensor by Zheng's research group. 49 The limit of detection (LOD) for this system was found to be 3 × 10 −5 M. Notably, in the year of 2023, our research group has also reported a valuable fluorescein functionalized dipyrromethane (DPM) based chemosensor for the selective detection of fluoride, phosphate and acetate ions over various other tested anions. 50 …”
Section: Introductionmentioning
confidence: 90%